Sexual violence: 10 years of case studies in a hospital in Northern Italy - Francesca Maghin; Michele Campagnari; Giuseppe Ricca; Adelaide Conti (SAGE Publishing, 2021)
Background: In the past twenty years, the fight against sexual violence has become a common goal of the entire European Union, due to a greater socio-cultural awareness of the population and the need to create guidelines for common action. Italian Law no. 66 of February 15, 1996 regarding the "Rules against sexual violence" which, with the appropriate amendments, is still in force today, defines 3 types of sexual offenses through the articles 609 of the Penal Code. Design and Methods: This study analyzes the cases relating to one of the hospitals in Northern Italy, during the decade January 2010 - December 2019, relating to suspected/reported cases of sexual violence, group sexual violence and sexual acts with minors. This study was carried out by acquiring information relating to subjects who had been victims of a sexual crime through the analysis of the consultations drawn up by specialist medical staff in the submentioned hospital. These consultations are defined by specific medical protocols that must be activated every time a victim of a suspected sexual offense comes into the Emergency Room (ER). The data were processed with descriptive analyzes, the qualitative variables were synthesized with absolute and percentage frequencies, while the quantitative variables with mean and interpolation of the data, to identify a trend line. In order to hypothesize the possible future trend of the phenomenon, data were collected relating to the type of crime according to the Penal Code, gender and age of the victim. This article also outlines future directions for improving research. Results: Our data show that females, of any age, are the most affected in all sexual crimes, often share home with their aggressor, usually a man, and in most cases, they come to the medical observation without any lesion on their body. Conclusions: In order to provide a global vision of the situation and of the diffusion throughout the territory, studies like this one could be carried out in various Italian provinces. Besides, we hope that the high degree of commitment on the part of society and institutions in combating sexual violence, through information campaigns and incitements to report, will lead in a few years to a reduction in the number of victims of repeated violence (especially in family contexts) and, consequently, also in the total number of acts of violence that comes to the attention of the healthcare facilities. Finally, primary prevention of sexual violence must begin early because a substantial portion is experienced at a young age. It will be necessary to prevent these forms of violence with strategies that address known risk factors for perpetration (e.g., low family support, high poverty, low parental education, absent or single parenting, parental substance abuse, domestic violence, low caregiver warmth), by changing social norms and behaviors and by identifying protective factors that could be strengthened.